A Pro-resolving Role for Galectin-1 in Acute Inflammation - Law, Hannah L.; Wright, Rachael D.; Iqbal, Asif J.; Norling, Lucy V.; Cooper, Dianne (Frontiers in Pharmacology, 2020)
Galectin-1 (Gal-1) exerts immune-regulatory and anti-inflammatory actions in animal models of acute and chronic inflammation. Its release into the extracellular milieu often correlates with the peak of inflammation suggesting that it may serve a pro-resolving function. Gal-1 is reported to inhibit neutrophil recruitment and induce surface exposure of phosphatidylserine, an ‘eat me’ signal on the surface of neutrophils, yet its role in resolution remains to be fully elucidated. We hypothesised that the anti-inflammatory and pro-resolving properties of Gal-1 are mediated through its ability to inhibit neutrophil recruitment and potentiate neutrophil clearance. To investigate this, a murine model of self-resolving inflammation was utilised to uncover the role of both the endogenous and exogenous protein using Gal-1 null mice and recombinant protein respectively. We found that peritoneal macrophages express increased Gal-1 during the resolution phase and enhanced neutrophil recruitment occurs in the early phases of zymosan peritonitis in Gal-1 null mice compared to their wildtype (WT) counterparts. Administration of recombinant Gal-1 following the peak of inflammation led to reduced neutrophil numbers at 24 and 48 hours, shortening the resolution interval from 39 to 14 hours. Gal-1 treatment also enhanced neutrophil apoptosis, indicating a pro-resolving action. Together these results indicate an important role for Gal-1 in the timely resolution of acute inflammation.